Analisis Konflik Sosial Pembangunan Pelabuhan Internasional Kijing terhadap Kehidupan Masyarakat Desa Sungai Kunyit Provinsi Kalimantan Barat - Alam Mahadika (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2020)
The purpose of this study is to analyze the emergence of social conflicts caused by the construction of the Kijing International Port which is located in Sungai Kunyit Village, Mempawah Regency, West Kalimantan. The data was collected by means of conducting literature studies and field observations. The results found, among others. Community residential land was evicted and turned into land for the construction of the Kijing International Port. There is a potential for loss of community jobs as fishermen and farmers because their lost waters and land are turned into the Kijing Port. The emergence of damage to community settlements due to the port construction process. Low compensation for community land. Insistence from the development party to sell people's land quickly. So this research suggests a multi-stakeholder dialogue that needs to be carried out so that conflicts can be resolved properly and with direction.